2019
DOI: 10.1097/aln.0000000000002730
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Degranulation and Fibroblast Activation in the Morphine-induced Spinal Mass

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background As the meningeally derived, fibroblast-rich, mass-produced by intrathecal morphine infusion is not produced by all opiates, but reduced by mast cell stabilizers, the authors hypothesized a role for meningeal mast cell/fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…In the light of the present study, it is tempting to speculate that some of these activities may be attributed to the scavenging function of ACKR3 68,69 . Recently, the orphan receptor MRGPRX2 (Mas-related GPCR X2 or MrgX2) was also proposed as an AOR 55,70,71 . It is expressed on mast cells and small diameter neurons in dorsal root and trigeminal ganglia and induces classical G protein signaling in response to micromolar concentrations of pro-dynorphin-derived peptides and well-known synthetic opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the present study, it is tempting to speculate that some of these activities may be attributed to the scavenging function of ACKR3 68,69 . Recently, the orphan receptor MRGPRX2 (Mas-related GPCR X2 or MrgX2) was also proposed as an AOR 55,70,71 . It is expressed on mast cells and small diameter neurons in dorsal root and trigeminal ganglia and induces classical G protein signaling in response to micromolar concentrations of pro-dynorphin-derived peptides and well-known synthetic opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal opiate use with drugs like morphine is usually impacted by the risk of producing space-occupying intrathecal masses through Mas-related G-protein coupled receptor (MRGPR) signaling. A recent study by the Yaksh group shows that PZM21 does not produce mast cell degranulation or activation of fibroblasts because it doesn’t activate MRGs, unlike morphine, suggesting that MOR biased ligands could be useful for intrathecal therapies [ 41 ].…”
Section: Mor Biased Agonismmentioning
confidence: 99%
“…(9) Current work has emphasized the role of a family of Mas-Related G-Protein Coupled Receptors (MRGP-r) in mediating opioid-receptor-independent degranulation of mast cells by morphine (29). In recent studies in the guinea pig, we found that two mu agonists, DMT-DALDA and PZM21, that are not activators of MRGP-r produce little or no mast cell degranulation, do not activate fibroblasts and when infused intrathecally do not produce intrathecal masses (30). Of note, it was recently reported that a spinal mass resected from a patient receiving 50 mg/mL morphine displayed particulates of morphine, in a loculated fluid-filled sac at the catheter tip, suggesting that at concentrations close to solubility in a buffered water environment with restricted diffusion access, particulate formation may occur, and may contribute to the local reaction (31).…”
Section: Role Of Meningeal Mast Cellsmentioning
confidence: 94%